BLOOD AS SPECTACLE: THE AESTHETICS OF VIOLENCE IN QUENTIN TARANTINO’S CINEMA - Rajkumar, Johnson (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Quentin Tarantino’s films, renowned for their stylized violence has long provoked debates over their aesthetic innovation and accusations of gratuitous brutality. This article analyses how Tarantino transforms violence into a postmodern aesthetic strategy in Kill Bill: Volume 1 & 2 (2003–2004), Inglourious Basterds (2009) and Django Unchained (2012). Drawing on Jean Baudrillard’s hyperreality, Fredric Jameson’s pastiche and Slavoj Zizek’s typology of violence, the study situates Tarantino’s work within discourses of postmodernism and cinema. Through close textual analysis, the article argues how imagery of violence in Tarantino’s films is used as spectacle and the aesthetics of the violence prioritises irony and performance over realism. At the same time, the analysis interrogates tensions surrounding historical revisionism and ethical spectatorship in Tarantino’s approach. The article argues that Tarantino’s cinema navigates the paradox of postmodern violence where it challenges moral panics about media effects while deploying violence as a hyper-stylized, symbolic language that reframes cultural narratives.